Features of the civil law status of tokenized property rights in the modern economic system - Leshchenko, Yulia (Український політико-правовий дискурс, 2025)
The relevance of this study is determined by the rapid expansion of asset tokenization technologies and the emergence of new models for the exercise of property rights within the digital economy. The transformation of economic relations under the influence of distributed ledger technologies has led to the appearance of new objects of civil circulation that require appropriate legal recognition, effective mechanisms of transfer, and reliable protection of the rights of market participants. At the same time, existing approaches to the regulation of tokenized property rights remain fragmented, creating a need for a deeper scientific understanding of their civil law nature and operational characteristics. The purpose of the article is to advance the scholarly understanding of the civil law status of tokenized property rights by clarifying their legal nature, examining the specific features of their circulation in the digital economy, and substantiating approaches to the improvement of their legal regulation and protection. Methods. The study employs both general scientific and special legal research methods, including formal-legal, systemic-structural, comparative-legal, logical-legal, and analytical methods. The research is based on international legal instruments, European Union regulations, Ukrainian legislation, and contemporary academic literature addressing digital assets and tokenization. Results. The conceptual and legal foundations of tokenized property rights were examined, and their place within the system of civil law relations was determined. The principal mechanisms and models of real-world asset tokenization were analyzed, and their impact on the transformation of property rights circulation in digital environments was identified. It was found that tokenization contributes to increased asset liquidity, broader access to investment opportunities, and the development of new forms of participation in economic value creation and distribution. It was demonstrated that tokenization transforms traditional ownership models through the fractionalization of proprietary interests, the separation of economic participation from direct control over assets, and the emergence of new forms of collective ownership. Key legal, regulatory, and practical challenges associated with the legal qualification of tokenized rights, cross-border circulation of digital assets, protection of token holders, application of smart contracts, and legal certainty of digital transactions were identified. Conclusions. The effective development of tokenized property rights requires the adaptation of traditional civil law institutions to the realities of the digital economy, the strengthening of legal mechanisms linking tokens with underlying assets, and the enhancement of safeguards for market participants. Future research should focus on the legal nature of digital control over assets, the civil law implications of smart contracts, dispute resolution mechanisms in decentralized environments, and the harmonization of international approaches to the regulation and protection of tokenized property rights.